Recognizing reflexivity among conservation practitioners. Issue 2 (20th February 2023) - Pienkowski, Thomas; Kiik, Laur; Catalano, Allison; Hazenbosch, Mirjam; Izquierdo‐Tort, Santiago; Khanyari, Munib; Kutty, Roshni; Martins, Claudia; Nash, Fleur; Saif, Omar; Sandbrook, Chris
Abstract: When deciding how to conserve biodiversity, practitioners navigate diverse missions, sometimes conflicting approaches, and uncertain trade‐offs. These choices are based not only on evidence, funders' priorities, stakeholders' interests, and policies, but also on practitioners' personal experiences, backgrounds, and values. Calls for greater reflexivity—an individual or group's ability to examine themselves in relation to their actions and interactions with others—have appeared in the conservation science literature. But what role does reflexivity play in conservation practice? We explored how self‐reflection can shape how individuals and groups conserve nature. To provide examples of reflexivity in conservation practice, we conducted a year‐long series of workshop discussions and online exchanges. During these, we examined cases from the peer‐reviewed and gray literature, our own experiences, and conversations with 10 experts. Reflexivity among practitioners spanned individual and collective levels and informal and formal settings. Reflexivity also encompassed diverse themes, including practitioners' values, emotional struggles, social identities, training, cultural backgrounds, and experiences of success and failure. Reflexive processes also have limitations, dangers, and costs. Informal and institutionalized reflexivity requires allocation of limited time and resources, can be hard to put into practice, and alone cannot solve conservation challenges. Yet, when intentionally undertaken, reflexive processes might be integrated into adaptive management cycles at multiple points, helping conservation practitioners better reach their goals. Reflexivity could also play a more transformative role in conservation by motivating practitioners to reevaluate their goals and methods entirely. Reflexivity might help the conservation movement imagine and thus work toward a better world for wildlife, people, and the conservation sector itself. Abstract : Reconocimiento de la reflexividad entre los practicantes de la conservación Resumen: Cuando se decide cómo conservar la biodiversidad, quienes la practican sortean varias misiones, algunas veces con enfoques contrastantes y compensaciones inciertas. Estas elecciones no se basan solamente en las evidencias, prioridades de los financiadores, los intereses de los actores y las políticas, sino también en las experiencias personales, formación y valores de los practicantes. En la literatura sobre las ciencias de la conservación han surgido llamados para una mayor reflexividad – la habilidad individual o grupal para examinarse a sí mismo en relación con sus acciones e interacciones con otros. Pero ¿cuál es el papel de la reflexividad en la práctica de la conservación? Para responder esto, exploramos cómo la autorreflexión puede determinar cómo ocurre la conservación individual y grupal de la naturaleza. Realizamos una serie de talleres de discusión e intercambios virtuales durante un año para ejemplificar la reflexividad en la práctica de la conservación. Durante estas sesiones examinamos casos de la literatura gris y revisada por pares, nuestras propias experiencias y conversaciones con diez expertos. La reflexividad de los practicantes abarcó niveles individuales y colectivos y escenarios formales e informales. La reflexividad también comprendió diferentes aspectos de los practicantes, como los valores, conflictos emocionales, identidad social, preparación, contexto cultural y experiencias exitosas y fallidas. Los procesos reflexivos también tienen limitaciones, riesgos y costos. La reflexividad informal e institucionalizada requiere la distribución de tiempo y recursos limitados, puede ser difícil de poner en práctica y no puede resolver los retos de conservación por sí sola. Aun así, cuando se realizan intencionalmente, los procesos reflexivos pueden integrarse a los ciclos de manejo adaptativo en varios puntos, lo que ayuda a quienes practican la conservación a lograr sus metas de mejor manera. La reflexividad también podría tener un papel transformador en la conservación al motivar a los practicantes a reevaluar completamente sus metas y métodos. La reflexividad podría ayudar al movimiento de conservación a imaginar, y por lo tanto trabajar para tener, un mundo mejor para la vida silvestre, las personas y el propio sector de la conservación. 【摘要】: 当决定如何保护生物多样性时, 保护实践者需要处理不同的任务, 有时要采用相互冲突的方法, 或面临不确定的利弊权衡。这些选择不仅基于证据、资助者的优先排序、利益相关者的利益及政策, 而且也基于保护实践者的个人经验、背景和价值观。保护科学文献中出现了对更多反身性的呼吁, 也就是个人或团体根据他们的行动和与他人的互动来反思自己的能力。然而, 反身性在保护实践中发挥了什么作用？本研究探讨了自我反思如何塑造个人和团体保护自然的方式。为了提供保护实践中反身性的例子, 我们进行了为期一年的一系列研讨会和在线交流。在这些活动中, 我们讨论了同行评议和灰色文献中的案例、我们自身的经验, 以及与十位专家的会谈。保护实践者之间的反身性跨越了个人和集体的层面以及非正式和正式的环境。反身性也包含了不同的主题, 包括保护实践者的价值观、情感挣扎、社会身份、训练、文化背景, 以及成功和失败的经验。反思的过程存在局限性、危险性和成本。非正式和制度化的反身性需要分配有限的时间和资源, 可能很难付诸实践, 而且不能独自解决保护挑战。然而, 如果有意进行反思, 该过程可以被整合到适应性管理周期的多个节点中, 帮助保护实践者更好地实现目标。反身性还可以通过激励保护实践者完全地重新评估其目标和方法, 在保护中发挥更大的变革作用。此外, 反身性可以帮助保护运动的构想, 从而为野生动物、人类和保护部门自身争取建立一个更好的世界。【翻译:胡怡思;审校:聂永刚】